Injury characteristics, mechanisms, and game circumstances in junior community-level Australian football - Indianna L. Franke; Andrea B. Mosler; Brooke E. Patterson; Kay M. Crossley; Patrick Clifton; Steven McPhail; Mark J. Scholes; Matthew G. King (JSAMS Plus)
Objective: Describe the injury characteristics, game circumstances, and immediate action and management of injuries sustained by boys and girls participating in junior community Australian football. Design: Cohort Study. Methods: All community junior Australian football players from one Victorian-based league were eligible to participate if they were injured during a game and presented to the gameday first aid medics. Injured players were subsequently followed up with a phone call to undertake an injury surveillance survey. The injury surveillance survey gathered information relating to the injury characteristics, game circumstances and management undertaken. Additionally, all players who sustained a head impact were asked about the presence or absence of concussion-related symptoms. Results: 439 players sustained an injury in the 2022 season, with 354 (80.6 ​%) participating in the survey. The head was the most frequently reported injured body region (n ​= ​194, 54.8 ​%), with approximately half (n ​= ​101) being a diagnosed or suspected sports-related concussion. The next three most frequently reported body regions were the ankle (n ​= ​29, 8.2 ​%), knee (n ​= ​24, 6.8 ​%), and shoulder (n ​= ​20, 5.6 ​%). Almost all injuries were acute onset (n ​= ​340, 96.0 ​%) and resulted from a contact-based mechanism (94.9 ​%, n ​= ​222 direct contact, n ​= ​114 indirect contact). Tackling was the most frequently reported game circumstance resulting in an injury (n ​= ​160, 45.2 ​%). Conclusion: The head was the most frequently reported injured body region, with approximately one in every two reported head impacts resulting in a diagnosed/suspected sports-related concussion. Injury prevention strategies that promote safety when tackling and being tackled may reduce the frequency of injury, warranting further investigation.